PENGARUH KOMISARIS INDEPENDEN DAN KOMITE AUDIT TERHADAP PENGURANGAN ASIMETRI INFORMASI DISEKITAR PENGUMUMAN LABA - Evi Gantyowati; Dhinar Adi Nugroho (Jurnal Siasat Bisnis, 2009)
This research examine the impact of Independent Commissioner and Independent Audit Committee to reduces information asymmetry around earnings announcement. The sample of this research is the firms that included Indonesian Capital Market Directory (ICMD) 2007. Based on purposive sampling method, the sample is 86 firms during the period of 2004–2006. The results of this research show that independent commissioner has a significant impact to the reducing of asymmetry information. Independent Audit Committee is not indicate has an impact and a correlation to asymmetric information, like the independent commissioner. There is no differences in asymmetric information between firms with independent audit committee and none.Keywords: Independent Commissioner, Independent Audit Committee, Asymmetry Information, Earnings Announcement, Trading Volume Activity (TVA)